Five-star or thumbs-up? The influence of rating system types on users' perceptions of information quality, cognitive effort, enjoyment and continuance intention. Issue 3 (5th June 2017) - Chen, Chi-Wen
Abstract : Purpose: Recent years have witnessed the development of a variety of rating systems but the authors have little knowledge about their impact on users' perceptions of information quality, cognitive decision effort, and enjoyment. The purpose of this paper is to understand the potential cognitive fit underlining the relationship between rating systems types (i.e. five-star, binary-visual, and binary-textual) and tasks (i.e. purchase-decision and browsing tasks) in the context of shopping websites. Design/methodology/approach: A total of 191 subjects were obtained. This study conducted an experiment with a 2×3 between-subject factorial design. The first dimension is a task that has two conditions (purchasing vs browsing). The second dimension is a type of rating system that has three different types (binary-textual, binary-visual, and five-star). Findings: The results show that the cognitive fit may occur when individuals use a five-star rating system to help them make a purchasing decision and when they use a binary-visual rating system while browsing. This fit might increase perceived information quality while decrease cognitive decision efforts, and in turn raise intention to adopt the systems. Moreover, five-star rating systems can make users feel more fun and enjoyment than binary-textual and visual rating systems, regardless of task type. Research limitations/implications: This study focuses on three main rating systems that are popular on shopping websites. Nevertheless, few other rating systems exist in the market such as unitary or ten-star rating systems. Further studies can consider other types of rating systems and address, in addition to representation, the issue of information granularity (i.e. unitary, binary, five-star, and ten-star rating systems). Practical implications: The results of this study could provide design principles for web designers in determining which rating systems best match the websites they are developing. If the websites or specific webpages are more utilitarian oriented (hedonic oriented), five-star rating systems (binary-visual rating systems) are more appropriate. Originality/value: This study contributes to the rating system literature by examining the cognitive fit underlining the relationship between rating systems types and tasks. Importantly, this study extends cognitive fit theory by considering affective responses, that is, perceived enjoyment and intention to continue to use.